Isobaric vapor-liquid equilibria of ternary lead-tin-antimony alloy system at 2 Pa - Xu J.; Gao J.; Kong L.; Xu B.; Yang B.; Liu D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this study, the experimental vapor–liquid equilibria data of the ternary Pb–Sn–Sb alloy system are determined using a new experimental method. The experimental VLE data passed the thermodynamic consistency test (Van Ness test), suggesting that the experimental results are reliable. The activities of the components of Pb–Sn–Sb ternary alloy and those of the corresponding three constituent binaries were calculated using the Wilson equation. The predicted values are in good agreement with the data determined from the experiments, and the average relative deviation and average standard deviation were smaller than ± 4.00% and ± 0.03 for all constituent binaries, respectively, which indicates that the Wilson equation is reliable for calculating the activity of the components of the Pb–Sn–Sb ternary alloy. The VLE data of the Pb– Sn and Sb–Sn binary alloys and Pb–Sn–Sb ternary alloy were calculated based on the VLE theory and the Wilson equation. The calculated VLE data were in good agreement with the data determined from the experiments, indicating that this method is reliable for calculating the VLE of alloy systems. The proposed study offers a valid method for analyzing the composition of products that are dependent on the distillation temperature and system pressure during vacuum distillation, which is of great significance to the experimental design of this process.